Effect of extruded corn flour addition on the quality characteristics of fine dried noodles. Issue 4 (28th March 2022) - Xu, Fei; Chen, Jie; Wang, Lei; Liu, Shuhang
Abstract: Background and Objectives: In the past decade, the nonwheat grain noodle has been increasingly popular in the consumer market. However, as pseudocereals lack gluten protein, the addition level of pseudocereal in the wheat dough is strictly limited due to the poor viscoelastic property and processability. Findings: In this study, to increase the addition level of corn in wheat, extrusion was used to modify corn flour's (CF's) physicochemical and rheological properties. Physicochemical, hydration, and structural property of extruded corn flour (ECF) were analyzed and compared with CF. Results showed that compared with CF, the content of moisture, fat, and starch of ECF decreased, the content of protein remained unchanged, while the content of reducing sugar, soluble dietary fiber, water solubility index, water absorption index, and viscosity characteristics significantly increased. Additionally, X‐ray diffraction (XRD) analysis and Fourier transform infrared spectra analysis demonstrated that the extrusion process disrupts the crystal structure of corn starch, the crystallinity of ECF decreased. In XRD analysis, the peak detected at around 20° confirmed the formation of the starch–lipid complex during the extrusion process. Conclusions: Different ECF and CF amounts were added to the dough and produced fine dried noodles. According to the tensile and scanning electron microscopy results, the ECF can improve the quality of dough and fine dried noodles. Significance and Novelty: The results indicated that ECF could effectively enhance the maize addition level in wheat/maize blended fine dried noodles without compromising fine dried noodles' quality.